Chlamydia pneumoniae Infection in Patients With Diffuse Panbronchiolitis and COPD - Miyashita, Naoyuki; Niki, Yoshihito; Nakajima, Masamitsu; Kawane, Hiroshi; Matsushima, Toshiharu (Chest, 1998)
To determine the possible association of Chlamydia pneumoniae infection with diffuse panbronchiolitis (DPB) and with COPD. Prospective case-control study. Division of Respiratory Diseases, Kawasaki Medical School Hospital. Fifteen DPB and 77 COPD patients who had acute exacerbations of respiratory conditions and 35 and 120 control subjects, respectively, matched for age, sex, and smoking status. Nasopharyngeal swabs and paired serum samples were obtained from all patients and control subjects for isolation and antibody testing of C pneumoniae. C pneumoniae was isolated from one DPB patient and from no COPD patients or control subjects. Serologic evidence of acute C pneumoniae infection was observed in one DPB patient (6.7%) and six COPD patients (7.8%). The prevalence and mean titer of C pneumoniae IgG and IgA antibodies were significantly higher in COPD patients than in control subjects (p< 0.001). However, no such differences were observed between DPB patients and control subjects. This study showed that C pneumoniae infection may be associated with acute exacerbations of COPD and that chronic C pneumoniae infection is common in COPD but not in DPB.